Characterization of the complications associated with plasma exchange for thrombotic thrombocytopaenic purpura and related thrombotic microangiopathic anaemias: a single institution experience. Issue 2 (10th October 2013) - McGuckin, S.; Westwood, J.‐P.; Webster, H.; Collier, D.; Leverett, D.; Scully, M.
<x xml:space="preserve">Abstract</x> Background Plasma exchange (PEX) is a life‐saving therapeutic procedure in patients with thrombotic thrombocytopaenic purpura (TTP) and other thrombotic microangiopathic anaemias (TMAs). However, it may be associated with significant complications, exacerbating the morbidity and mortality in this patient group. Study Design and Methods We reviewed all PEX procedures over a 72‐month period, following the exclusive introduction of solvent–detergent double viral‐inactivated plasma in high‐volume users, such as TTP, in the United Kingdom (UK). We documented allergic reactions to plasma, citrate reactions, complications relating to central venous access insertion and venous thrombotic events (VTE) in 155 patient episodes and >2000 PEX procedures. Results The overall complication rate was low. Allergic plasma reactions occurred in 6·45% of the cohort with only one episode of acute anaphylaxis. Similarly, VTEs were 6·45%, not significantly greater than in medical patients receiving thromboprophylaxis, despite added potential risk factors in TTP. Citrate reactions were the most frequent complication documented, but toxicity was significantly reduced by administration of further calcium infusions during the PEX procedure. There were no serious central line infections and no catheter thrombosis. Conclusion Our data confirms that PEX continues to be a life‐saving procedure in the acute TTP setting and, the procedure was not associated with an increased mortality and limited morbidity.